SEKAMI SEBAGAI PEMBENTUK SPIRITUALITAS KOMUNAL DI ERA DIGITAL UNTUK GENERASI ALPHA DI PAROKI ST. ALFONSUS MARIA DE LIQUORI LEWOTALA - Dangga, Mateus; Lelu, Skolastika; Aran, Alfonsus Mudi (Jurnal Masalah Pastoral, 2025)
SEKAMI activities are an important mission in maturing children's faith through the packaging of spiritual activities in the current era of digitalization. Through this activity, of course, it will bring children's faith closer to God in accordance with the teachings of the Catholic Church. However, problems are still found in the parishes.  One of them in Lewotala Parish was found that many children have not been actively involved in activities both in joint prayer activities, as well as liturgical activities such as Eucharistic celebrations on Sundays. Therefore, the purpose of this study is to find out and describe the role of SEKAMI in forming Communal Spirituality in the Digital Era for the Alpha Generation. The method used is a type of qualitative research with a descriptive approach. Interview data collection techniques, observations, and documentation. The subjects in this study were 9 informants. The results found that SEKAMI plays an important role in shaping the spirituality of the alpha generation in the digital era. Through spiritual and social activities, children are taught Christian values, concern for others, and the spirit of brotherhood. SEKAMI must continue to be a forum for fostering faith and teaching Christian values, as well as encouraging children to live the spirit of 2D2K (Prayer, Donation, Sacrifice, and Testimony). Thus, SEKAMI children can grow in faith and become witnesses of Jesus Christ, as well as use technology positively.